1988
DOI: 10.1192/bjp.152.5.660
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Chinese Hamilton Depression Rating Scale

Abstract: The reliability and validity of the Chinese version of the 17-item Hamilton Depression Rating Scale (CHDS) was assessed. Interrater reliability was excellent, the item total-score correlations were good, and the internal reliability was satisfactory. The concurrent validity was tested by correlating the CHDS score with the Global Assessment Scale score; the strong negative correlation found indicated that the CHDS reflects the overall level of disability. Five distinct factors were generated by principle-compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
187
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(200 citation statements)
references
References 6 publications
4
187
0
Order By: Relevance
“…The high reliability of HAMD-17 has been verified by 49 years, whose pooled internal reliability was 0.789 [26]. It has an internal reliability of 0.72 or higher in China [27]. …”
Section: Methodsmentioning
confidence: 99%
“…The high reliability of HAMD-17 has been verified by 49 years, whose pooled internal reliability was 0.789 [26]. It has an internal reliability of 0.72 or higher in China [27]. …”
Section: Methodsmentioning
confidence: 99%
“…The caregivers of the demented subjects were interviewed with the Chinese version of the Alzheimer's disease behavioral pathology rating scale (BEHAVE-AD) (Reisberg et al, 1987) concerning the behavioral disturbance in the preceding four weeks. The patients' Chinese mini-mental state examination (CMMSE) (Chiu et al, 1994) and the Chinese Hamilton rating scale of depression (CHDS) (Weiner et al, 1997;Zheng et al, 1988) also were completed. A research assistant or an author (VPYL), who was blind to the rating of BEHAVE-AD, interviewed the caregiver with the Chinese neuropsychiatric inventory (CNPI).…”
Section: Assessmentmentioning
confidence: 99%
“…The scale has good inter-rater reliability, item total-score correlations, and internal reliability reported. The concurrent validity was tested by correlating the HDRS score with the Global Assessment Scale score (Endicott et al, 1976); the strong negative correlation found indicated that the HDRS reflects the overall level of disability The cut-off score of !10 is recommended as an indication of depression (range: 1-30) (Zheng et al, 1988).…”
Section: Measurementsmentioning
confidence: 99%